Improvement of production and stability of silk degumming protease by Bacillus sp. C4 SS-2013 - Nisa Romsomsa (Science Faculty of Chiang Mai University, 2019)
Optimization of silk degumming protease production from isolated Bacillus sp. C4 SS-2013 was performed by batch culture in a stirred tank bioreactor. Central composite design (CCD) was applied to optimize aeration and agitation rates and predicted by response surface methodology (RSM). The maximum protease production (P) of 1,890 U/mL and a specific production rate (qp) of 21,412 U/g/h were obtained at the agitation and aeration rates of 400 rpm and 2 vvm which corresponded to a KLa value of 182.16 h-1. These experimental values were coincident with the predicted values and the models were proved to be adequate with the coefficient of determination (R2) of P, qp, and KLa equal to 0.950, 0.931 and 0.881, respectively. The pH-stat fed-batch culture could increase the silk degumming protease production to 4,437 U/mL (2.35-fold) and qp to 36,820 U/g/h (1.72-fold). The addition of 10 mM CaCl2 into the crude protease and storage at 4OC for 8 weeks could maintain its activity at about 52 % of the initial activity. Both the agitation and aeration rates significantly affected the protease production, specific protease production rate and KLa. The improvement of production and stabilization during storage of silk degumming protease were achieved in our study which has potential for industrial applications.